2014
DOI: 10.1016/j.ydbio.2014.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breakage in the vertebrate embryo: When does it happen and how does it work?

Abstract: Asymmetric development of the vertebrate embryo has fascinated embryologists for over a century. Much has been learned since the asymmetric Nodal signaling cascade in the left lateral plate mesoderm was detected, and began to be unraveled over the past decade or two. When and how symmetry is initially broken, however, has remained a matter of debate. Two essentially mutually exclusive models prevail. Cilia-driven leftward flow of extracellular fluids occurs in mammalian, fish and amphibian embryos. A great dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
108
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(117 citation statements)
references
References 131 publications
(195 reference statements)
0
108
0
9
Order By: Relevance
“…These findings suggest that the origin of organ laterality can be rooted in actomyosin activity. Thus, it seems that nodal flow might be a secondary mechanism to enforce or further amplify L/R asymmetric information but that actomyosin-mediated asymmetric morphogenesis of the L/R organizer or chiral organs is directly involved in organismal chiral symmetry breaking It should also be noted that other, earlier forms of chiral cytoskeletal symmetry breaking have been reported in vertebrates, however, different than for invertebrates, these earlier asymmetric processes do most likely not constitute decisive events for organismal L/R patterning [253]. Notably, Danilchik et al have shown that cleaving Xenopus embryos undergo a dramatic large-scale torsion, with the actomyosin cortex shearing in an exclusively counterclockwise direction [254].…”
Section: Chiral Symmetry Breaking In Vertebratesmentioning
confidence: 99%
“…These findings suggest that the origin of organ laterality can be rooted in actomyosin activity. Thus, it seems that nodal flow might be a secondary mechanism to enforce or further amplify L/R asymmetric information but that actomyosin-mediated asymmetric morphogenesis of the L/R organizer or chiral organs is directly involved in organismal chiral symmetry breaking It should also be noted that other, earlier forms of chiral cytoskeletal symmetry breaking have been reported in vertebrates, however, different than for invertebrates, these earlier asymmetric processes do most likely not constitute decisive events for organismal L/R patterning [253]. Notably, Danilchik et al have shown that cleaving Xenopus embryos undergo a dramatic large-scale torsion, with the actomyosin cortex shearing in an exclusively counterclockwise direction [254].…”
Section: Chiral Symmetry Breaking In Vertebratesmentioning
confidence: 99%
“…The node of the cow embryo is also enclosed in subchordal mesoderm [82], suggesting multiple vertebrates use ciliaindependent mechanisms to establish LR asymmetry. Second, several events that impact LR asymmetry described in the frog embryo occur prior to the appearance and function of cilia in the LRO [83,84]. These include signalling between ectoderm and migrating mesoderm cells mediated by the heparan sulfate proteoglycan Syndecan 2 during gastrulation stages [85,86] and ion gradients established by the H ĂŸ /K ĂŸ -ATPase [87] and vacuolar-type H ĂŸ -ATPase [88] proton pumps that could drive asymmetric localization of determinants, such as serotonin [89], at early cleavage stages.…”
Section: (C) Laterality Cues For Cilia?mentioning
confidence: 99%
“…Motile cilia move extracellular fluids, mediate cellular motility and play essential roles during development, tissue homeostastis and reproduction (reviewed by Choksi et al, 2014b;Gerdes et al, 2009;Nigg and Raff, 2009). In vertebrate embryos, motile cilia in the left-right organiser rotate and generate a leftward flow of the extracellular fluid, which is translated into left-right asymmetry of visceral organs (reviewed by Blum et al, 2014;Nonaka et al, 1998;Takeda et al, 1999). Coordinated beating of motile cilia on epithelia of the lung is required for airway clearance (Jain et al, 2010;Stannard and O'Callaghan, 2006).…”
Section: Introductionmentioning
confidence: 99%